Pengaruh Kompetensi, Independensi dan Pengalaman Kerja Auditor Terhadap Kualitas Audit Pada Perwakilan BPKP Provinsi Jawa Barat - Dailibas Dailibas; Nasution Nasution (UNSIKA (Universitas Singaperbangsa Karawang), 2019)
The main problem of this research are: (1) How much influence of auditor's competence to audit quality at BPKP West Java Province. (2) How much influence auditor independence to audit quality at BPKP West Java Province. (3) How much influence of auditor work experience to audit quality at BPKP West Java Province. (4) How much influence the independence, competence, and experience of auditor work on audit quality at BPKP West Java Province. The purpose of this study to determine the general description of the Competence, Independence and Work Experience Auditors simultaneously affect the quality of audits at BPKP Representatives West Java Province. The research method used descriptive by using quantitative approach. The results of this study prove that the Competence, Independence and Working Experience Auditor significantly influence the quality of audits conducted by auditors BPKP Representative West Java Province. Suggestions to be addressed are: (1) To strengthen the competence of auditors to attend seminars more often, to increase formal education and training on audits and other disciplines to support audit implementation, as well as opportunities to attend courses or improvement of professional education, (2) ). To increase independence in order for the auditor to avoid complicating interests with the parties being examined, and to limit repeated audits to the same inspection object each year. (3). To improve audit work experience for auditor to always perform audit, and in conducting of audit supported by making adequate audit work papers and end by compiling audit report result.